30 days to market mastery : a step-by-step guide to profitable trading - Bernstein, Jacob, 1946- (Hoboken, N.J. : John Wiley, 2007)
A solid foundation for those looking to succeed in today's market. An excellent book for new traders, 30 Days to Market Mastery outlines an easy-to-understand and easy-to-implement approach to learning how to trade. This book covers the fundamentals of how to structure trades in a disciplined fashion, so as to avoid vague decisions and acting on unclear trading signals.
Includes index.
oif 16/10/14
Loan
Keywords: Futures; Futures market -- Examinations, questions, etc